Increased prevalence of irritant hand eczema in health care workers in a dermatological clinic due to increased hygiene measures during the SARS-CoV-2 pandemic - Reinholz, Markus; Kendziora, Benjamin; Frey, Surina; Oppel, Eva Maria; Rueff, Franziska; Clanner-Engelshofen, Benjamin Maximilian; Heppt, Markus; French, Lars Einar; Wollenberg, Andreas (European Journal of Dermatology, 2021)
Background: Hand hygiene measures in the general population and in health care workers have increased considerably since the outbreak of the COVID-19 pandemic. Objectives: To investigate the prevalence and symptoms of hand eczema, as well as hygiene measures and concepts of care, in German health care workers. Materials & Methods: This was an observational questionnaire study to investigate hygiene and skin care habits, as well as the prevalence and symptoms of hand eczema in 66 nurses and doctors of our dermatology department before and during the SARS-CoV-2 pandemic. Results: Hand washing and hand disinfection procedures increased significantly during the COVID-19 pandemic. Self-diagnosed hand eczema was reported by 33% of the participants, with a median duration of 14 days. The majority of staff currently affected by hand eczema were free of eczema a month previously (82%) and would treat their skin condition with emollients (77%). Erythema, scaling, burning and fissures were reported by 66.1% of the participants and were classified as predominant signs of toxic-irritant hand dermatitis rather than contact allergy. Conclusion: Overall, the SARS-CoV-2 pandemic has led to a significant increase in the incidence of signs of irritant hand eczema despite intensified emollient use as a preventive measure. Awareness of the prevalence of hand eczema in health care workers in Germany during the COVID-19 pandemic should be raised, and preventive measures should be intensified.
CRIS-Team Scopus Importer:2021-08-20
Keywords: corona virus; COVID-19; dermatology; hand eczema; health care workers; SARS-CoV-2